2021
DOI: 10.2196/29809
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Professional Accounts on Social Networks Twitter and ResearchGate and the Number of Scientific Publications and Citations Among Anesthesia Researchers: Observational Study

Abstract: Background Social networks are now essential tools for promoting research and researchers. However, there is no study investigating the link between presence or not on professional social networks and scientific publication or citation for a given researcher. Objective The objective of this study was to study the link between professional presence on social networks and scientific publications/citations among anesthesia researchers. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
7
0
2
Order By: Relevance
“…The increase in social media use among the #pedsanes community mirrors the use of the #regionalanesthesia and #regionalanaesthesia hashtags, especially during conferences and throughout the COVID pandemic 11–14,20 . The adoption of social media such as Twitter is likely inevitable as it has played a significant role in disseminating information and is associated with a higher citation rate among French anesthesia researchers 4–6,8 . Of interest, our study reports a higher retweet rate of 61.2%, when compared with users of the #anesthesia and #regionalanesthesia/#regionalanaesthesia hashtags who retweeted at lower rates of 33% and 49%, respectively 12,13 .…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The increase in social media use among the #pedsanes community mirrors the use of the #regionalanesthesia and #regionalanaesthesia hashtags, especially during conferences and throughout the COVID pandemic 11–14,20 . The adoption of social media such as Twitter is likely inevitable as it has played a significant role in disseminating information and is associated with a higher citation rate among French anesthesia researchers 4–6,8 . Of interest, our study reports a higher retweet rate of 61.2%, when compared with users of the #anesthesia and #regionalanesthesia/#regionalanaesthesia hashtags who retweeted at lower rates of 33% and 49%, respectively 12,13 .…”
Section: Discussionmentioning
confidence: 62%
“…The use of social media within the medical field has rapidly evolved over the past two decades, with Twitter being one of the most common platforms of engagement 1,2 . Social media has proven to be an essential source of information dissemination, allowing innovations to be shared before peer‐reviewed publication while increasing research reach compared with scientific journal publication alone 3–8 . It is also an important source of professional networking and, in some instances, has been used as public education, advocacy, and support resource 9–11 .…”
Section: Introductionmentioning
confidence: 99%
“…(Watson et al, 2019) A few published empirical studies examined the effects of empirical data on other research fields. (Antoniou et al, 2015;Betz et al, 2021;Harsh et al, 2021;Mutka et al, 2021;Wilson et al, 2020) A study by Clavier et al (2021) found that the number of tweets an arti-…”
Section: Introductionmentioning
confidence: 99%
“…(Watson et al, 2019) A few published empirical studies examined the effects of empirical data on other research fields. (Antoniou et al, 2015; Betz et al, 2021; Harsh et al, 2021; Mutka et al, 2021;Wilson et al, 2020) A study by Clavier et al (2021) found that the number of tweets an article received was moderately correlated to the citation count of the article published in 2008 and 2011 in Journal of Medical Internet Research (JMIR). Results of the study suggest that the tweets within the first 3 days of the articles publication can predict if the article is going to be a highly cited article in JMIR.…”
Section: Introductionmentioning
confidence: 99%
“…1 It is a social network used for professional purposes by many medical societies, researchers, and professionals in the fields of anesthesiology and intensive care. 2–4 Thus, we recently described that 24% of prolific authors publishing in the field of anesthesiology journals have a Twitter account and that 17% of French anesthesiology, intensive care, and emergency medicine health care workers use Twitter at least once a week. 5,6 This new network use should increase with the arrival of younger physicians since it was reported that 35% of medical students used Twitter for teaching purposes.…”
mentioning
confidence: 99%